Application of Corticosteroids in Dentistry: A Review - Souptik Satpathi; Yogesh V. Rathod; Kamil N. Rajpari; Rohit Kandlikar; Y. Rajiv Kumar; Arti Gachake; Pratik Surana (Journal of Pharmacy and Bioallied Sciences)
Corticosteroids are crucial in dentistry for their anti-inflammatory and immunosuppressive properties, aiding in managing conditions such as oral lichen planus, recurrent aphthous stomatitis, and post-operative inflammation. By inhibiting pro-inflammatory mediators and immune cell activity, they offer significant symptomatic relief and promote healing. However, potential systemic and local side effects necessitate cautious application. This article explores the use of corticosteroids in routine dental practice.